Determining the Predominant Lesion in Patients With Severe Aortic Stenosis and Coronary Stenoses: A Multicenter Study Using Intracoronary Pressure and Flow. (December 2019) - Ahmad, Yousif; Vendrik, Jeroen; Eftekhari, Ashkan; Howard, James P.; Cook, Christopher; Rajkumar, Christopher; Malik, Iqbal; Mikhail, Ghada; Ruparelia, Neil; Hadjiloizou, Nearchos; Nijjer, Sukhjinder; Al-Lamee, Rasha; et al.
Abstract : Background: Patients with severe aortic stenosis (AS) often have coronary artery disease. Both the aortic valve and the coronary disease influence the blood flow to the myocardium and its ability to respond to stress; leading to exertional symptoms. In this study, we aim to quantify the effect of severe AS on the coronary microcirculation and determine if this is influenced by any concomitant coronary disease. We then compare this to the effect of coronary stenoses on the coronary microcirculation. Methods: Group 1: 55 patients with severe AS and intermediate coronary stenoses treated with transcatheter aortic valve implantation (TAVI) were included. Group 2: 85 patients with intermediate coronary stenoses and no AS treated with percutaneous coronary intervention were included. Coronary pressure and flow were measured at rest and during hyperemia in both groups, before and after TAVI (group 1) and before and after percutaneous coronary intervention (group 2). Results: Microvascular resistance over the wave-free period of diastole increased significantly post-TAVI (pre-TAVI, 2.71±1.4 mm Hg·cm·s −1 versus post-TAVI 3.04±1.6 mm Hg·cm·s −1 [ P =0.03]). Microvascular reserve over the wave-free period of diastole significantly improved post-TAVI (pre-TAVI 1.88±1.0 versus post-TAVI 2.09±0.8 [ P =0.003]); this was independent of the severity of the underlying coronary stenosis. The change in microvascular resistance post-TAVI was equivalent to that produced by stenting a coronary lesion with an instantaneous wave-free ratio of ⩽0.74. Conclusions: TAVI improves microcirculatory function regardless of the severity of underlying coronary disease. TAVI for severe AS produces a coronary hemodynamic improvement equivalent to the hemodynamic benefit of stenting coronary stenoses with instantaneous wave-free ratio values <0.74. Future trials of physiology-guided revascularization in severe AS may consider using this value to guide treatment of concomitant coronary artery disease.